Role of p27 in differentiating follicular adenoma and follicular carcinoma of the thyroid - Deuri, Bimanjyoti; Tabassum, Musfika; Lahkar, Nandinee (International Journal of Research in Medical Sciences, 2021)
Background: Thyroid neoplasms represent a broad spectrum of tumors with different biologic behaviour. Although investigations like thyroid function tests, scintigraphy and ultrasonography were routinely used for the diagnosis of thyroid nodules, they could not discriminate between benign and malignant lesions. The present study is undertaken to assess the expression of cell cycle protein such as p27kip1 (p27) in thyroid neoplasms which might be useful in predicting behaviour of various thyroid neoplasms and aid in their diagnosis. Aim of the study was to assess the expression of p27 and its role in differentiating follicular adenoma and follicular carcinoma of the thyroid. Methods: The present study was undertaken to evaluate the expression of p27 in thyroid neoplasms with the help of immunohistochemical analysis over a period of 1 year. The study was conducted on archival blocks retrieved from the Department of Pathology, SMCH. 19 thyroid neoplasms were diagnosed (7 benign, 12 malignant) and IHC expression of p27 was studied. Results: There was over-expression of p27 staining in case of follicular adenoma whereas malignant lesions showed underexpression on p27 staining. P27 expression was significantly different in follicular adenoma and follicular carcinoma of the thyroid. Conclusions: The role of p27 in differentiating benign and malignant thyroid neoplasms may prove it to be a candidate marker if combined with other additional investigations like radionuclide scan or using a broad panel of IHC markers. This may provide more insight into the behaviour of tumors in a detailed manner.